Pendampingan Sekolah Adiwiyata: Pengelolaan Lingkungan Berkelanjutan Melalui Edukasi dan Aksi - Asiah, Nur; Harjoni, Harjoni; Negara, Hasan Sastra (Universitas Pahlawan Tuanku Tambusai, 2024)
The Adiwiyata School program aims to create a school environment that cares and is environmentally cultured. However, many schools face challenges in its implementation, such as the lack of understanding and involvement of the school community. This service was conducted through participatory mentoring methods, including training, workshops, and hands-on practice involving teachers, students, and school staff. The results showed an 80% increase in knowledge of the Adiwiyata concept among participants, the formation of an Adiwiyata implementation team, and the implementation of the initial steps of the program such as waste management and greening. The program successfully increased the awareness and involvement of the school community in sustainable environmental management.